THE IMPACT OF COVID-19 ON THE SUPPLY CHAIN MANAGEMENT OF THE E-COMMERCE INDUSTRY IN INDONESIA - Yusuf, Salman
COVID-19 had created a major shift in how conventional, brick-to-mortar, and any business in general to operate. This creates a stagnated process in the flow of operations in different sectors of businesses. Convenient physical activities are heavily impacted due to the health protocols relevant in different places, especially in Indonesia. Having been considered to have a strict protocol for COVID-19, business activities receive a heavy hit in Indonesia. With the changes occurring in the business industry, several factors are required for organizations to survive with the sudden change. One of the key elements is to implement the use of digital technology. With the ever growing phenomena of digitalization, implementing these matter becomes a necessity especially amid pandemic. The business sector itself can be divided into multiple industries with different companies benefiting from digital technology in different ways. Talking specifically in this paper, in correspondence to the adaptation of the business sector, a growing industry has shed light during this age, which is e-commerce. Being a platform that is based electronically through the internet, the usage of e-commerce has grown significantly. Globally, e-commerce has become one of the most relied methods of purchase, however this paper will specifically dissect one of the world’s most overlooked e-commerce markets, Indonesia. Being the biggest user of e-commerce in South East Asia, Indonesia has the potential to utilize this business sector to its fullest. The impact of the pandemic will directly impact the e-commerce businesses in Indonesia through its supply chain management sector. With the concurrent growth of digitalization and the regulations of COVID-19 in Indonesia, the supply chain management has the ability to improve its work processes by implementing digital technology. With the many variables of digital technology, implementing it to the functions of supply chain management will differ from business to business. This research will dissect the different utilization of digital technology in the supply chain management of e-commerce businesses in Indonesia, such as the use of Big Data Analytics, increased usage of Internet of Things (IoT) and the utilization of Cloud Computing. It will also investigate the impact that COVID-19 has on the e-commerce businesses in Indonesia through the lenses of both customer and seller. This research will utilize a descriptive design framework with a longitudinal time scale. It will consist of a quantitative data through secondary method of research to analyze and compare the e-commerce industry before and after the pandemic. With the concurrent method of analysis and results, the growth of the e-commerce industry has shown to be directly impacted by COVID-19. The outbreak had significantly increase the demand for e-commerce in Indonesia. The section of supply chain management itself plays a big role in this sector of business as it creates a pedigree of solution during the pandemic. It leads to the innovation and improvement of the e-commmerce businesses through the use of digitalization and technology in its supply chain management. As a recommendation, for further research, due to the limited resources of data gathering, implementing a primary data set from Indonesia’s e-commerce players for the analysis will improve the study by making it more direct and specific.